Da organiseret kriminalitet blev indført til Danmark - Joi Bay (Nordisk Tidsskrift for Kriminalvidenskab)
Organized crime was imported to Denmark within a few years during the 1990s when well-known forms of crime were redefined as organized crime. This article describes how organized crime was constructed as a social and criminal problem and how a certain, broad understanding of organized crime was institutionalized. The vehicle for the introduction of the concept organized crime and the implementation of organized crime as a phenomenon in Denmark was - on one hand - the growth of outlaw motorcycle gangs and - on the other hand - the increasing European Union cooperation in the legal field.